Species II - Medak, Peter; Mancuso, Frank; MGM Home Entertainment Inc.; Viva Video (Santa Monica, Calif distributed by MGM Home Entertainment; distributed in the Philippines by Viva Video, 2005)
Just when you thought the threat of alien colonization was over ... the deadliest species from deep space is back and more menacing than ever before.
Originally released as a motion picture in 1998.
Based on characters created by Dennis Feldman.
Director of photography, Matthew F. Leonetti; music, Edward Shearmur; editor, Richard Nord.
Michael Madsen, Natasha Henstridge, Marg Helgenberger, Mykelti Williamson, George Dzundza, James Cromwell.
MPAA rating: R
VCD
Keywords: Life on other planets -- Drama